LEGAL CERTAINTY OF ONLINE MOTORCYCLE TAXI DRIVERS IN THE PERSPECTIVE OF COMPARISON WITH MALAYSIA - Wadrianto, Glori Kyrious; Winanti, Atik (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The emergence of the gig economy, driven by advancements in technology, carries notable legal consequences, particularly in Indonesia. This research highlights the lack of legal clarity concerning online transportation (ojek online) drivers, who represent a key segment of gig workers. These drivers are designated as "partners," a classification that fails to grant them comprehensive legal protections or certainty. The aim of this study to examine the legal standing of ojek online drivers amidst this regulatory gap, focusing on their rights as workers under Indonesian law and how it compares to Malaysia’s Gig Workers Act 2025. To conduct this analysis, the study utilizes a normative juridical method, incorporating a conceptual approach, a case study approach, and a comparative analysis. The research draws from various sources including primary legal materials, secondary legal materials, and tertiary legal materials, which are evaluated prescriptively. The results reveal that the lack of explicit legal regulations governing ojek online drivers in Indonesia creates significant potential for uncertainty. Malaysia’s Gig Workers Act 2025 may provide an exemplary framework for regulatory improvements in Indonesia. Establishing a definitive legal structure would not only enhance certainty and fairness for approximately seven million online motorcycle taxi drivers but also benefit other gig workers in Indonesia, whose numbers are anticipated to rise alongside technological growth. The establishment of a separate classification for gig workers—including online ride-hailing drivers—as implemented in Malaysia, could serve as a reference for Indonesia in providing legal certainty without eliminating the flexibility that is inherent to the gig economy phenomenon.